Enhancing visual perception of sports quality in rhythmic gymnastics routine by increasing congruence between music and movement - Loo, Fung Chiat; Loo, Fung Ying; Chua, Yan Piaw; Ismail, Md Jais (Horizon Research Publishing, 2022)
The use of music in sports routines that involve choreography is inevitable, and the appropriateness between the two is taken into account for awarding points in competitions. In dance, theatre, or in firm music, the use of music in choreography displays the subjectivity of interpretation to a certain extent due to preferences, background of audience, coach, and composer. However, more scientific and fundamental aspects shared between music and movement can provide a better perception of a particular routine. This study reports an experiment on a rhythmic gymnastics routine to investigate whether an increased congruence between music and movement enhances the perception of sports quality from a musical perspective. In the experiment, the original music accompaniment was changed with a new composition to increase the congruence between music and movement using six parameters including tempo, rhythm, phrasing, accent, direction, and dynamic. Fifty-two undergraduate music majors evaluated two videos of the same routine in a questionnaire regarding the qualities of the performance. Apart from motivation, the results show that the sports qualities with the new accompaniment were significantly perceived better than the original version.